ANTIOXIDATIVE ACTIVITY OF SURFACE COMPLEX OF POLY-(3-AMINOPROPYL)-SYLOXAN WITH COPPER (II) IONS - M. A. Stashkevych; L. V. Gayova; O. V. Stechenko; L. F. Osinska (Bogomolets National Medical University, 2015)
Summary. The present study is devoted to the search of the new biological properties of poly-(3-aminopropyl)- syloxan surface complex with copper (II) ions (Cu2+- PAPS) which exhibits high antibacterial activity toward strains which cause gastric and duodenal ulcer. The relevance of the usage of copper containing complex is stipulated by the fact that copper plays the important role in the various metabolic processes in human body: in biological oxidation, synthesis of macroergic compounds, formation of connective tissue proteins, iron metabolism. Copper (II) is a cofactorof enzymes which are important for the protection of tissues from the active forms of oxygen - these are superoxide dismutase, cerruloplasmin, xantineoxidase, ascorbate oxidase etc. So copper containing compounds protect living cells from the oxidative stress, lipids and proteins oxidation, especially in biomembranes. The antioxidative activity of poly-(3- aminopropyl)-syloxan complex with copper (II) ions in the model systems with the usage of liposomes derived from the egg yolk and antiradical activity of this complex that was determined by the inhibition of p-nitrozolium chloride reduction by anion-radical generated in the photochemical system. The statistically significant decrease of the formation of malondialdehyde from the phospatidylcholine of the egg yolk after the addition of the investigational preparation with copper was demonstrated. The mechanism of the antioxidative activity of this preparation is obviously associated with the inhibition of the organic radicals, transformation of peroxide to the stable products of oxidation: alcohols, aldehydes, ketones. The obtained results evidence the moderate antioxidative and antiradical activity of the complex Cu2+-PAPS (up to 80% as compared to ionol and up to 60% as compared to cerruloplasmin). The obtained data confirm the reasonability of the further preclinical screening of the poly-(3-aminopropyl)-syloxan complex with copper (II) ions.